Hubungan Antara Pendekatan Konseling Berpusat Pada Anak (Pendekatan Client Centered) Dengan Efektivitas Konseling Individual Pada Siswa SMA (Studi Kasus Di SMA Dhammasavana, SMA Dharma Suci, dan SMA Triratna) - Jeny Harianto; Jo Priastana; Mettadewi Mettadewi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
With the era of digital development 4.0 provides improved lives for individuals to be able to adjust well. The role of the counselor adds importance to students as a shelter for students. Help needs counselors as a place to share opinions Center Center helps students to express their feelings to the counselor.This study aims to find conversations or relationships between asking for child-centered counseling (asking for ClientCentered) by using individual counseling in high school students. Read the full story which is pleased to introduce students who are efficient and effective is very important to know, understand where the motivation and capacity of students to make changes. This research is a quantitative type of ex-post-facto research, discussing the type of causal research (discussion research), which is a study that discusses data collection to determine whether there is a relationship and the relationship between variables or more (Widarto, 2013: 3). The subjects of the study were high school students Tri Ratna and Dharma Suci, Dhammasvana High School located in West Jakarta. The sampling technique is done by simple random sampling (Simple Random Sampling), and sample calculation is determined using the Slovin formula. The data used in this study are secondary data and primary data. Secondary data were obtained by conducting literature studies and relevant literature studies. Meanwhile, primary data were obtained using an instrument in the form of a questionnaire. Questionnaires are used to obtain client-centered therapy scores and meet individual counseling. The results showed the difference between a clientcentered counseling model (child-centered counseling) with individual counseling approval